Method for cleaning transparent gallium nitride material
Through the steps of alternating acid-base cleaning, cleaning of ammonium sulfide solution and ultraviolet lamp irradiation, the problem of removing surface pollution of transparent GaN materials on non-sapphire substrates is solved, and the effect of efficient pollution removal is achieved while ensuring that transparency does not decrease. It is suitable for the purpose of improving pollution. Application in laboratory or small-scale research.
Patent Information
- Application Number
- CN202411624596.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-07
AI Technical Summary
The existing technology is difficult to effectively remove pollution from the surface of transparent GaN materials of non-sapphire substrates while ensuring that transparency does not decrease. The traditional cleaning process is complex, the equipment requirements are high, and the cost is high, making it difficult to apply in laboratory or small-scale research. .
The acid-base alternate cleaning method is adopted, including concentrated hydrochloric acid and strong alkali solution alternately, followed by ammonium sulfide solution, and finally ultraviolet lamp irradiation and acetone cleaning to remove surface contamination.
On the premise that the transparency of gallium nitride material does not decrease or the transparency of the gallium nitride material does not decrease by more than 5%, it effectively removes surface contamination, which is suitable for applications in laboratory or small-scale research, and has a low cost.
Smart Images

Figure CN119400685A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor material cleaning processes, and in particular relates to a method for cleaning a transparent gallium nitride material. Background Art
[0002] Transparent GaN on non-sapphire substrates will inevitably produce various impurities on the surface during growth and use. For example, due to polarization adsorption when standing in the air or after several tests, processing and other processes, its surface will be contaminated to varying degrees, thus affecting the subsequent experiments and even affecting the properties of materials and devices.
[0003] In addition, for non-sapphire substrate transparent GaN samples, improper cleaning may cause the transparency of the material to decrease. The cleaning process is usually required to ensure that the transparency of the material does not decrease or the transparency decreases by no more than 5%. Due to its special requirements for transparency, traditional semiconductor cleaning processes are not suitable for cleaning non-sapphire substrate transparent GaN. In addition, the industrial-grade cleaning process is relatively complicated, and the requirements and costs for equipment are relatively high. Conventional laboratories or small-scale research experiments should not use industrial cleaning methods because it will lead to unnecessary cost increases and usually do not have the corresponding equipment conditions. Therefore, in conventional laboratories or small-scale research experiments, when the surface of non-sapphire substrate transparent GaN is contaminated, how to use a relatively convenient cleaning method to remove the contamination while ensuring high transparency is one of the problems that need to be solved urgently. Summary of the invention
[0004] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions: One of the purposes of the present invention is to provide a method for cleaning a transparent gallium nitride material, comprising: The transparent gallium nitride material is alternately cleaned with an acid and a strong alkali solution in sequence, wherein the acid includes concentrated hydrochloric acid, concentrated nitric acid or concentrated sulfuric acid, wherein each cleaning time of the concentrated hydrochloric acid is 10-25 seconds, each cleaning time of the concentrated nitric acid or concentrated sulfuric acid is 7-8 seconds, and each cleaning time of the strong alkali solution is 10-15 seconds; After the acid-base alternating cleaning, the transparent gallium nitride material is cleaned with an ammonium sulfide solution, and the cleaning time of the ammonium sulfide solution is within 50 seconds; After washing with the ammonium sulfide solution, drying the transparent gallium nitride material and then irradiating it with an ultraviolet lamp; After UV irradiation, the samples were cleaned with acetone and then dried for storage.
[0005] The cleaning method provided by the present invention can effectively remove contamination on the surface of a transparent gallium nitride material while maintaining the transparency of the gallium nitride material (the transparency is not reduced or the transparency is reduced by no more than 5%). The reagents used in the cleaning method are all easily available reagents, have low equipment requirements, and are low in cost. The cleaning method is suitable for use in contaminated gallium nitride materials generated in small-scale research experiments such as laboratories, and can achieve effective cleaning and recycling of gallium nitride materials without the need for process-level cleaning equipment and at low cost.
[0006] Among them, the cleaning time of each strong alkaline solution and ammonium sulfide solution is more important for maintaining transparency. If the cleaning time of each strong alkaline solution and ammonium sulfide solution is too long, the transparency of the gallium nitride material will be significantly reduced, and it will become translucent or opaque. The purpose of using ammonium sulfide solution for cleaning is to saturate the GaN surface dangling bonds to the maximum extent, passivate the surface, and prevent the surface from being oxidized again. If the cleaning time of ammonium sulfide solution is too long, ammonium sulfide will remain and corrode the surface, causing the surface to be contaminated again or even yellow. The high-energy photons of ultraviolet rays can change the chemical bond state of the semiconductor surface, making the originally firmly adsorbed impurities unstable, and then acetone can be used to remove them more thoroughly.
[0007] In some embodiments, the acid-base alternating cleaning includes first acid cleaning, then strong alkaline solution cleaning, and repeating 5 to 7 times. Short-term acid cleaning and alkaline cleaning cannot effectively remove contamination on the surface of gallium nitride (such as oxides, residual metal impurities, etc.). However, if the transparent gallium nitride material is immersed in acid or alkali for a long time, the surface of gallium nitride will be etched and the transparency will be seriously reduced. The present invention can ensure that the surface contamination is washed away without reducing the transparency by performing acid-base alternating cleaning and controlling the time of each cleaning. In addition, in some embodiments, the acid-base alternating cleaning is first cleaned with concentrated hydrochloric acid and then cleaned with a strong alkaline solution. The strong alkaline solution can remove the hydrochloric acid attached to the surface of gallium nitride and remove the chloride ions that may exist on the surface.
[0008] In some embodiments, the concentration of the concentrated hydrochloric acid, concentrated nitric acid, and concentrated sulfuric acid is 68-98 wt %.
[0009] In some embodiments, the concentration of the strong alkali solution is 50-70 wt %. The strong alkali includes, for example, sodium hydroxide, potassium hydroxide, etc., but is not limited thereto.
[0010] In some embodiments, the cleaning time of the ammonium sulfide solution is 15-30 seconds. If the ammonium sulfide cleaning time is too short, the GaN surface dangling bonds cannot be effectively saturated to passivate the surface. If the time is too long, the transparency of GaN is reduced. It is more suitable to be more than 50 seconds, preferably within 15-30 seconds.
[0011] In some embodiments, the concentration of the ammonium sulfide solution is 20-25 wt %.
[0012] In some embodiments, the ultraviolet light irradiation time is 5-20 minutes. Ultraviolet light has high energy, and ultraviolet light irradiation can stimulate chemical reactions on the surface of semiconductors, causing chemical changes in impurity molecules or atoms adsorbed on the surface, promoting the decomposition of organic pollutants adsorbed on the surface, generating volatile substances, and then being removed.
[0013] In some embodiments, the ultraviolet lamp irradiation is performed in a mixed atmosphere containing argon and ozone, and the volume ratio of argon to ozone is 1:1-2.5, for example, 1:1 or 1:1.5, 1:2.5.
[0014] In some embodiments, cleaning the transparent gallium nitride material with acetone specifically includes: soaking the transparent gallium nitride material in an acetone solution at a temperature of 10-25° C. for 2-5 minutes.
[0015] In some embodiments, the cleaning method further comprises: before performing the acid-base alternating cleaning, wiping the surface of the transparent gallium nitride material to be cleaned.
[0016] In some embodiments, the cleaning method further comprises: after the acid-base alternating cleaning is completed, placing the transparent gallium nitride material in ethanol for ultrasonication for 5-10 minutes, and then cleaning with ammonium sulfide solution. Ultrasonic cleaning in ethanol can be combined with acid-base alternating cleaning and ammonium sulfide solution cleaning to further ensure that impurities on the material surface are fully removed.
[0017] After the transparent gallium nitride material is treated with the acid, strong alkali solution, ammonium sulfide solution, ethanol or acetone solution, the transparent gallium nitride material is rinsed with deionized water and / or the transparent gallium nitride material is ultrasonically cleaned with deionized water before proceeding to the next step. These reagents are prevented from staying on the surface of the gallium nitride material for a long time to damage it, and the mixing of different washing reagents is prevented from affecting the washing effect.
[0018] In some embodiments, the method for drying the transparent gallium nitride material includes: first rinsing the transparent gallium nitride material with ethanol, and then blowing it with an inert gas (such as one or more of argon and nitrogen) to obtain a dry transparent gallium nitride material. Dehydrating with ethanol first and then blowing with an inert gas can accelerate the drying process and prevent the gallium nitride surface from absorbing pollutants such as dust in the air again due to natural drying.
[0019] In some embodiments, for transparent gallium nitride materials with residual glue on the surface, such as PMMA, PVA or other photoresists, the residual glue is removed before the acid-base alternating cleaning.
[0020] In some embodiments, the method for removing the residual adhesive includes at least one of a and b: a. Soften the residual glue on the surface of the transparent gallium nitride material at a temperature of 250-350°C in an inert atmosphere; b. Soak the transparent gallium nitride material in cold acetone at room temperature and hot acetone at 50-65°C to dissolve the residual glue on its surface; c. placing the transparent gallium nitride material in water for ultrasonic cleaning; d. Place the transparent gallium nitride material in water and heat it to 65-75°C for 50-120 minutes; e. Annealing the transparent gallium nitride material in a mixed atmosphere containing hydrogen and argon at a temperature of 450-650° C. for 20-30 minutes; f. Use argon plasma to strip off the residual glue on the surface of the transparent gallium nitride material.
[0021] In some embodiments, the step of removing the residual adhesive includes sequentially performing steps ae, or performing step f.
[0022] In some embodiments, the cleaning method is performed in a fume hood.
[0023] In some typical embodiments, the cleaning method comprises the following steps: (1) Use dust-free lens cleaning paper dipped in ethanol and / or acetone to wipe the transparent GaN material; (2) using concentrated hydrochloric acid and strong alkaline solution to perform acid-base alternating cleaning on the transparent gallium nitride material in turn, wherein the cleaning time of each concentrated hydrochloric acid cleaning is 10-25 seconds, and the cleaning time of each strong alkaline solution cleaning is 10-15 seconds; and the acid-base alternating cleaning is first performed with concentrated hydrochloric acid cleaning, and then with strong alkaline solution cleaning, and is repeated 5 to 7 times; (3) using an ammonium sulfide solution to clean the transparent gallium nitride material, wherein the cleaning time of the ammonium sulfide solution is within 50 seconds; (4) first rinsing the transparent gallium nitride material with ethanol, and then drying it with an inert gas to obtain a dry transparent gallium nitride material; (5) In a mixed atmosphere of oxygen-containing ozone and argon, a dried transparent gallium nitride material is irradiated with an ultraviolet lamp; (6) After the UV light irradiation is completed, the transparent gallium nitride material is immersed in an acetone solution at a temperature of 10-25°C for 5-20 minutes, and then dried and stored.
[0024] Furthermore, after the transparent gallium nitride material is contacted with concentrated hydrochloric acid, a strong alkaline solution, an ammonium sulfide solution, an ethanol or an acetone solution in the above steps, the transparent gallium nitride material is rinsed with deionized water, and / or the transparent gallium nitride material is ultrasonically cleaned with deionized water before proceeding to the next step.
[0025] The above steps (1) to (6) can fully remove impurities on the surface of gallium nitride while ensuring that its transparency does not decrease.
[0026] Compared with the prior art, the present invention has at least the following beneficial effects: the method provided by the present invention is suitable for cleaning transparent gallium nitride materials, and can effectively remove pollutants and impurities on the surface of gallium nitride while ensuring that the transparency of the gallium nitride material does not decrease or the transparency decreases by no more than 5%; the cleaning method is suitable for contaminated gallium nitride materials generated in small-scale research experiments such as laboratories, and can achieve effective cleaning and recycling of gallium nitride materials without the need for industrial-grade cleaning equipment and at low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 is a process flow chart of cleaning a transparent gallium nitride material in one embodiment of the present invention; Figure 2 It is a transparent gallium nitride material to be cleaned with contaminated surface; Figure 3 The method of Example 1 is used to Figure 1 Photo of the gallium nitride material after cleaning; Figure 4 The conventional semiconductor cleaning process of Comparative Example 5 is used to Figure 1 Photo of the gallium nitride material after cleaning; Figure 5 The method in Comparative Example 1 is used to Figure 1 Photo of the gallium nitride material after cleaning; Figure 6 The method in Comparative Example 2 is used to Figure 1 Photo of the gallium nitride material after cleaning; Figure 7 The method in Comparative Example 3 is used to Figure 1 Photo of the gallium nitride material after cleaning. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.
[0030] Unless otherwise specified, the raw materials and reagents used in the present invention are all commercially available. The reagents used in the following examples of the present invention are as follows: Concentrated hydrochloric acid: analytical grade, mass percentage 85%; sodium hydroxide: analytical grade, mass percentage>90%; ammonium sulfide: analytical grade, mass percentage <20%; anhydrous ethanol: analytical grade, mass percentage>99%; deionized water: 500ml; acetone: analytical grade, mass percentage 99%.
[0031] Example 1 This embodiment provides a method for cleaning a transparent gallium nitride material, which specifically includes the following steps: (1) Surface wiping: Place the GaN to be cleaned on a clean glass slide, wrap clean dust-free lens paper with the flat-tip tweezers, dip in anhydrous ethanol and wipe the GaN surface, wipe for 5 minutes each time, repeat three times, and replace with new dust-free lens paper each time; then, replace with new flat-tip tweezers, wrap clean dust-free lens paper, dip in acetone and wipe the GaN surface, wipe for three minutes each time, repeat twice; After wiping, place the GaN in a clean beaker filled with ultrapure water and ultrasonicate it twice in an ultrasonic cleaner for five minutes each time; (2) Acid-base alternating cleaning: Take 85% concentrated hydrochloric acid and pour it into a beaker. The volume of concentrated hydrochloric acid should be enough to slightly immerse the upper surface of GaN. Use a clean beaker to prepare 5 mol / I sodium hydroxide solution. The volume of sodium hydroxide solution should be enough to slightly immerse the upper surface of GaN. Then take a clean beaker and fill it with 50 ml of deionized water to rinse the sample. Grasp the two ends of the GaN material with tweezers, first place it in a beaker filled with concentrated hydrochloric acid, gently rinse it for 10 seconds and immediately take it out; then, immediately place it in a beaker filled with deionized water and gently rinse it for 5 seconds to wash off the hydrochloric acid remaining on its surface; then place it in a beaker filled with sodium hydroxide solution, gently rinse it for 10 seconds and take it out; then immediately place it in the same beaker filled with deionized water to rinse it clean, and repeat the above steps 5 times; The material was then placed in a new beaker containing alcohol and ultrasonically cleaned in an ultrasonic cleaning machine for 10 minutes. After cleaning, the GaN was rinsed with running deionized water, and then a new beaker was replaced, the GaN was placed in the new beaker, deionized water was poured in, and ultrasonic cleaning was performed with deionized water for 3 times, each time for 3 minutes. (3) Ammonium sulfide cleaning: Pour a 25wt% ammonium sulfide solution into a beaker, place GaN into the beaker, and perform ultrasonic cleaning for 30 seconds; After cleaning, pour the ammonium sulfide waste liquid into a dedicated waste liquid bucket, rinse the GaN with running deionized water for 1 minute, and then use deionized water for ultrasonic cleaning 3 times, 2 minutes each time; (4) Quick drying: Rinse the GaN with ethanol for one minute, then quickly blow dry the GaN surface with argon. Dehydrating with ethanol and blowing with argon can accelerate the drying process and prevent the adsorption of dust and other impurities in the air during the natural drying process); (5) Place the cleaned transparent GaN material into a glass tube, introduce a mixed gas of ozone and argon in a volume ratio of 1:1, and then turn on the ultraviolet light for 20 minutes; After irradiation, the GaN sample was immersed in a cold acetone solution for 5 minutes, and this process was repeated three times until the surface was completely free of contamination. Finally, it was rinsed with anhydrous ethanol, the surface was quickly dried with argon gas, and then packed in a box.
[0032] Example 2 This embodiment provides a method for cleaning a transparent gallium nitride material, and its process flow chart is as follows: Figure 1 As shown, the specific steps include the following: (1) Surface wiping: Place the GaN to be cleaned on a clean glass slide, wrap clean dust-free lens paper with the flat-tip tweezers, dip in anhydrous ethanol and wipe the GaN surface, wipe for 5 minutes each time, repeat three times, and replace with new dust-free lens paper each time; then, replace with new flat-tip tweezers, wrap clean dust-free lens paper, dip in acetone and wipe the GaN surface, wipe for three minutes each time, repeat twice; After wiping, place the GaN in a clean beaker filled with ultrapure water and ultrasonicate it twice in an ultrasonic cleaner for five minutes each time; (2) Acid-base alternating cleaning: Take 85% concentrated hydrochloric acid and pour it into a beaker. The volume of concentrated hydrochloric acid should be enough to slightly immerse the upper surface of GaN. Use a clean beaker to prepare 5 mol / I sodium hydroxide solution. The volume of sodium hydroxide solution should be enough to slightly immerse the upper surface of GaN. Then take a clean beaker and fill it with 50 ml of deionized water to rinse the sample. Grasp the two ends of the GaN material with tweezers, first place it in a beaker filled with concentrated hydrochloric acid, gently rinse it for 25 seconds and immediately take it out; then, immediately place it in a beaker filled with deionized water and gently rinse it for 5 seconds to wash off the hydrochloric acid remaining on its surface; then place it in a beaker filled with sodium hydroxide solution, gently rinse it for 15 seconds and take it out; then immediately place it in the same beaker filled with deionized water and rinse it clean, and repeat the above steps 7 times; The material was then placed in a new beaker containing alcohol and ultrasonically cleaned in an ultrasonic cleaning machine for 10 minutes. After cleaning, the GaN was rinsed with running deionized water, and then a new beaker was replaced, the GaN was placed in the new beaker, deionized water was poured in, and ultrasonic cleaning was performed with deionized water for 3 times, each time for 3 minutes. (3) Ammonium sulfide cleaning: Pour a 20wt% ammonium sulfide solution into a beaker, place GaN into the beaker, and perform ultrasonic cleaning for 50 seconds; After cleaning, pour the ammonium sulfide waste liquid into a dedicated waste liquid bucket, rinse the GaN with running deionized water for 1 minute, and then use deionized water for ultrasonic cleaning 3 times, 2 minutes each time; (4) Quick drying: Rinse the GaN with ethanol for one minute, then quickly blow dry the GaN surface with argon. Dehydrating with ethanol and blowing with argon can accelerate the drying process and prevent the adsorption of dust and other impurities in the air during the natural drying process); (5) Place the cleaned transparent GaN material into a glass tube, introduce a mixed gas of ozone and argon in a volume ratio of 1:1, and then turn on the ultraviolet lamp for 5 minutes; After irradiation, the GaN sample was immersed in an acetone solution at room temperature for 5 minutes, and this process was repeated three times until the surface was completely free of contamination. Finally, the sample was rinsed with anhydrous ethanol, the surface was quickly dried with argon gas, and the sample was packed in a box.
[0033] Example 3 Example 3 provides a method for cleaning a transparent gallium nitride material having PMMA or PVA adhesive residues on its surface: (1) Surface wiping: Place the GaN to be cleaned on a clean glass slide, wrap clean dust-free lens paper with the flat-tip tweezers, dip in anhydrous ethanol and wipe the GaN surface, wipe for 5 minutes each time, repeat three times, and replace with new dust-free lens paper each time; then, replace with new flat-tip tweezers, wrap clean dust-free lens paper, dip in acetone and wipe the GaN surface, wipe for three minutes each time, repeat twice; After wiping, place the GaN in a clean beaker filled with ultrapure water and ultrasonicate it twice in an ultrasonic cleaner for five minutes each time; (2) Removal of residual glue: a. Place GaN in a clean quartz beaker, fill the beaker with pure argon, seal it with clean tin foil, and then poke several small holes with pointed tweezers. Then place the quartz beaker on a heating table, adjust the temperature of the heating table to 300°C, and heat for 5 minutes to fully soften the adhesive on the GaN surface for subsequent cleaning and removal; the density of argon gas is 1.4 times that of air, which can exhaust air to the maximum extent to prevent impurities in the air from contaminating the surface at high temperatures, and also prevent oxygen in the air from reacting with the surface. The purpose of piercing holes after sealing with tin foil is to prevent the high-temperature expansion gas from bursting the seal; b. Place the GaN sample in a clean beaker and soak it in cold acetone at 25°C for 30 minutes; replace the beaker with a new one, place the GaN sample in hot acetone at 60°C, heat it to 60°C in a water bath, and keep it in a constant temperature water bath for 30 minutes. Repeat this three times, replacing the beaker each time; acetone is a strong solvent that can dissolve most glues including PMMA; c. Place GaN in a clean beaker filled with deionized water and clean it in an ultrasonic cleaner for three times, each time for 1 minute, and replace the beaker each time; d. Place GaN in a clean beaker filled with deionized water, heat it in a water bath to 70°C, and keep it for 50 minutes. Repeat twice, replacing a new beaker each time. This step can continue to remove glue such as PVA. e. Rinse the GaN with ethanol for 1 minute, then quickly blow dry its surface with argon to obtain dry GaN; place the transparent GaN in a tube furnace, first evacuate three times, then drive out the gas with pure argon at 40 ml / min for 20 minutes, then turn off the argon, and introduce a mixed atmosphere of hydrogen and argon. Set the tube furnace program in the mixed atmosphere to rise to 550°C in 25 minutes, keep the temperature constant in the mixed atmosphere for two hours, then quickly cool down to 100°C in 30 minutes, and then cool down naturally; After executing ae in sequence, the residual glue on the GaN surface is removed; (3) Acid-base alternating cleaning: Take 85% concentrated hydrochloric acid and pour it into a beaker. The volume of concentrated hydrochloric acid should be enough to slightly immerse the upper surface of GaN. Use a clean beaker to prepare 5 mol / I sodium hydroxide solution. The volume of sodium hydroxide solution should be enough to slightly immerse the upper surface of GaN. Then take a clean beaker and fill it with 50 ml of deionized water to rinse the sample. Grasp the two ends of the GaN material with tweezers, first place it in a beaker filled with concentrated hydrochloric acid, gently rinse it for 15 seconds and immediately take it out; then, immediately place it in a beaker filled with deionized water and gently rinse it for 5 seconds to wash off the hydrochloric acid remaining on its surface; then place it in a beaker filled with sodium hydroxide solution, gently rinse it for 12 seconds and take it out; then immediately place it in the same beaker filled with deionized water and rinse it clean, and repeat the above steps 6 times; The material was then placed in a new beaker containing alcohol and ultrasonically cleaned in an ultrasonic cleaning machine for 10 minutes. After cleaning, the GaN was rinsed with running deionized water, and then a new beaker was replaced, the GaN was placed in the new beaker, deionized water was poured in, and ultrasonic cleaning was performed with deionized water for 3 times, each time for 3 minutes. (4) Ammonium sulfide cleaning: Pour a 25wt% ammonium sulfide solution into a beaker, place GaN into the beaker, and perform ultrasonic cleaning for 40 seconds; After cleaning, pour the ammonium sulfide waste liquid into a dedicated waste liquid bucket, rinse the GaN with running deionized water for 1 minute, and then use deionized water for ultrasonic cleaning 3 times, 2 minutes each time; (5) Quick drying: Rinse the GaN with ethanol for one minute, then quickly blow dry the GaN surface with argon. Dehydrating with ethanol and blowing with argon can accelerate the drying process and prevent the adsorption of dust and other impurities in the air during the natural drying process); (6) The transparent GaN material with the residual glue removed is placed in a glass tube, and a mixed gas of ozone and argon in a volume ratio of 1:1 is introduced. Then, an ultraviolet lamp is turned on for 20 minutes, and then it is cleaned with acetone to obtain a clean transparent GaN material, which is then packed in a box.
[0034] Example 4 Example 4 is basically the same as Example 1, and the only difference of Example 4 is that the ultraviolet lamp irradiation is carried out in an argon atmosphere, and ozone is not introduced. The rest is implemented in the same way as Example 1.
[0035] Comparative Example 1 Comparative Example 1 is substantially the same as Example 1, except that step (2) of Comparative Example 1 is: Take 85% concentrated hydrochloric acid and pour it into a beaker. The volume of concentrated hydrochloric acid should be enough to slightly immerse the upper surface of GaN. Then take a clean beaker and fill it with 50ml of deionized water to rinse the sample. Use tweezers to pick up both ends of the GaN material, place them in a beaker filled with concentrated hydrochloric acid, soak them for 60 seconds, then take them out; then immediately place them in a beaker filled with deionized water to rinse them; The material was then placed in a new beaker filled with alcohol and put into an ultrasonic cleaner for ultrasonic cleaning for 10 minutes. After cleaning, the GaN was rinsed with running deionized water, and then a new beaker was replaced, the GaN was placed in the new beaker, deionized water was poured in, and ultrasonic cleaning was performed with deionized water for 3 times, each time for 3 minutes.
[0036] The remaining steps are implemented in the same manner as in Example 1.
[0037] Comparative Example 2 Comparative Example 2 is substantially the same as Example 1, except that step (2) of Comparative Example 2 is: Use a clean beaker to prepare a 5 mol / I sodium hydroxide solution. The volume of the sodium hydroxide solution should be enough to slightly submerge the GaN surface. Then take a clean beaker and fill it with 50 ml of deionized water to rinse the sample. Use tweezers to pick up both ends of the GaN material, put them into a beaker filled with sodium hydroxide solution, soak them for 60 seconds, then take them out; then immediately put them into a beaker filled with deionized water to rinse them; The material was then placed in a new beaker containing alcohol and ultrasonically cleaned in an ultrasonic cleaning machine for 10 minutes. After cleaning, the GaN was rinsed with running deionized water, and then a new beaker was replaced, the GaN was placed in the new beaker, deionized water was poured in, and ultrasonic cleaning was performed with deionized water for 3 times, each time for 3 minutes.
[0038] Comparative Example 3 is substantially the same as Example 1, except that the time for ammonium sulfide cleaning in step (3) of Comparative Example 2 is 60 seconds, and the rest is carried out in the same manner as Example 1.
[0039] Comparative Example 4 The only difference between Comparative Example 4 and Example 1 is that the ultraviolet light irradiation step is not performed in Comparative Example 4.
[0040] Comparative Example 5 The transparent gallium nitride material is cleaned using a conventional semiconductor cleaning process, which is based on Kern W. Handbook of semiconductor wafer cleaning technology. New Jersey: Noyes Publication 1993:111-196.
[0041] Figure 2 It is a transparent gallium nitride material with contaminated surface, and its transparency is almost 100%. Figure 3 The gallium nitride material is cleaned by the cleaning method of Example 1, the surface is cleaned, and the transparency is the same as before cleaning. Figure 4 The gallium nitride material was cleaned by the conventional semiconductor cleaning process of comparative example 5, and it was found that the transparency decreased after cleaning.
[0042] Figure 5 The gallium nitride material was cleaned by the method in Comparative Example 1. It was found that after continuous cleaning in concentrated hydrochloric acid for 60 seconds, the transparency of the material decreased and the surface was etched. Figure 6 The gallium nitride material was cleaned by the method in Comparative Example 2. It was found that after continuous cleaning in a sodium hydroxide solution for 60 seconds, the transparency of the material decreased. Figure 7The gallium nitride material was cleaned by the method in comparative example 3. It was found that after continuous cleaning in ammonium sulfide solution for 60 seconds, the transparency of the material decreased. This indicates that cleaning in concentrated hydrochloric acid, strong alkali solution, and ammonium sulfide solution for too long will lead to reduced transparency of the material, but too short a cleaning time cannot completely remove the contamination on the surface of the material. The present invention can effectively remove the contamination on the surface of the material while ensuring that the transparency of the material does not decrease or decreases by no more than 5% by performing multiple acid-base alternating cleaning and ammonium sulfide cleaning, and strictly controlling the cleaning time of each step, so that the gallium nitride material can be reused.
[0043] The present invention finds by comparing Example 1 and Comparative Example 4 that ultraviolet light irradiation can effectively remove pollutants. This may be because ozone can react with organic pollutants on the surface of the material under ultraviolet light irradiation, and ultraviolet rays directly act on the surface. Short-wavelength ultraviolet light can be absorbed by organic pollutants, causing their chemical bonds to break, thereby decomposing macromolecules into smaller fragments or directly converting them into a gas state; the two work together to accelerate the decomposition and removal of pollutants; this process can achieve a cleanliness level close to the atomic level, and even affect the atomic structure of the surface layer, reduce surface defects and improve interface quality. In addition, by comparing Example 1, Example 4 and Comparative Example 4, it is found that the cleaning effect of ultraviolet irradiation is better when ozone is introduced, indicating that ozone and ultraviolet light irradiation have a certain synergistic effect. It can be seen that in a cleaning process with higher requirements, it is preferred to use ultraviolet light irradiation in a mixed atmosphere of ozone and argon.
[0044] For transparent gallium nitride materials with residual adhesives such as PMMA and PVA on the surface, Example 3 further adds a residual adhesive removal step based on the cleaning process. It is found that the cleaning process combined with the above-mentioned residual adhesive removal method can effectively remove the residual adhesive and other contamination on the surface of the material while ensuring that the transparency is not reduced or reduced by no more than 5%. In addition, the present invention also replaces the residual adhesive removal steps ae in Example 3 with: placing the gallium nitride material in a plasma treatment instrument, treating it in an argon atmosphere for 120 seconds to 5 minutes, and using the residual adhesive to react with plasma to achieve the stripping of the residual adhesive on the surface of the GaN material. This method can also maintain the transparency without decreasing.
[0045] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0046] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0047] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another element.
Claims
1. A method for cleaning a transparent gallium nitride material, characterized in that: include: The transparent gallium nitride material is alternately cleaned with an acid and a strong alkali solution in sequence, wherein the acid includes concentrated hydrochloric acid, concentrated nitric acid or concentrated sulfuric acid, wherein each cleaning time of the concentrated hydrochloric acid is 10-25 seconds, each cleaning time of the concentrated nitric acid or concentrated sulfuric acid is 7-8 seconds, and each cleaning time of the strong alkali solution is 10-15 seconds; After the acid-base alternating cleaning, the transparent gallium nitride material is cleaned with an ammonium sulfide solution, and the cleaning time of the ammonium sulfide solution is within 50 seconds; After washing with the ammonium sulfide solution, drying the transparent gallium nitride material and then irradiating it with an ultraviolet lamp; After UV irradiation, the samples were cleaned with acetone and then dried for storage.
2. The cleaning method according to claim 1, characterized in that: The acid-base alternating cleaning includes first cleaning with an acid solution and then cleaning with a strong alkaline solution, and repeating this process 5 to 7 times; and / or, the concentration of the concentrated hydrochloric acid, concentrated nitric acid and concentrated sulfuric acid is 68-98wt%; And / or, the concentration of the strong alkaline solution is 50-70wt%.
3. The cleaning method according to claim 1, characterized in that: The cleaning time of the ammonium sulfide solution is 15 to 30 seconds; And / or, the concentration of the ammonium sulfide solution is 20-25wt%.
4. The cleaning method according to claim 1, characterized in that: The UV lamp irradiation time is 5-20min; And / or, the ultraviolet lamp irradiation is carried out in a mixed atmosphere containing argon and ozone, and the volume ratio of argon to ozone is 1:1-2.5; And / or, using acetone to clean the transparent gallium nitride material specifically includes: soaking the transparent gallium nitride material in an acetone solution at a temperature of 10-25° C. for 2-5 minutes.
5. The cleaning method according to claim 1, characterized in that: Also includes: Before performing the acid-base alternating cleaning, wiping the surface of the gallium nitride material to be cleaned; And / or, after the acid-base alternating cleaning is completed, the transparent gallium nitride material is placed in ethanol for ultrasonication for 5-10 minutes, and then cleaned with an ammonium sulfide solution.
6. The cleaning method according to claim 5, characterized in that: After the transparent gallium nitride material is treated with the acid, strong alkali solution, ammonium sulfide solution, ethanol or acetone, the transparent gallium nitride material is rinsed with deionized water and / or the transparent gallium nitride material is ultrasonically cleaned with deionized water before proceeding to the next step.
7. The cleaning method according to claim 1, characterized in that: The method for drying the transparent gallium nitride material comprises: firstly washing the transparent gallium nitride material with ethanol, and then drying it with an inert gas.
8. The cleaning method according to claim 1, characterized in that: For the transparent gallium nitride material with residual glue on the surface, the residual glue is removed before the acid-base alternating cleaning.
9. The cleaning method according to claim 8, characterized in that: The method for removing the residual glue comprises at least one of af: a. Softening the residual glue on the surface of the transparent gallium nitride material at a temperature of 250-350° C. in an inert atmosphere; b. Soaking the transparent gallium nitride material in cold acetone at room temperature and hot acetone at 50-65° C. to dissolve residual glue on the surface thereof; c. placing the transparent gallium nitride material in water for ultrasonic cleaning; d. placing the transparent gallium nitride material in water and heating it to 65-75° C. for 50-120 min; e. Annealing the transparent gallium nitride material in a mixed atmosphere containing hydrogen and argon at a temperature of 450-650° C. for 20-30 min; f. Using argon plasma to peel off the residual glue on the surface of the transparent gallium nitride material.
10. The cleaning method according to claim 9, characterized in that: The step of removing the residual glue includes sequentially performing steps ae, or performing step f.